Prevalence and antimicrobial-resistant characterization of Bacillus cereus isolated from ready-to-eat rice products in Eastern China - Chen, Jiancai; Zhang, Junyan; Zhan, Li; Chen, Honghu; Zhang, Zhen; Huang, Cheng; Yue, Min (Frontiers in Microbiology, 2022)
Bacillus cereus is a major food-borne bacterial pathogen in the world, which can cause diarrhea and emetic syndrome. This study aimed to reveal the quantitative prevalence of B. cereus in ready-to-eat (RTE) rice products in Eastern China and to gain essential information on the characteristics of B. cereus isolates. A total of 91 out of the 1071 samples were positive for B. cereus. The contamination level of B. cereus in 0.5 % of RTE rice product samples outnumbered 103 CFU/g. The number of B. cereus attained 105−106 CFU/g in one sample. The distribution patterns of virulence genes in B. cereus isolates were identified. 84.6% of the B. cereus isolates had at least one enterotoxin or emetic toxin gene. The predominant pattern was XXV. 9.9% of isolates belonged to it and possessed one enterotoxin gene entFM. The occurrence rate of hblACD and nheABC was 36.3% and 47.3%, respectively. Antimicrobial susceptibility tests revealed a high resistance rate toward penicillin, and 23.1% of the isolates were multi-drug resistant. B. cereus isolates were genotyped by using ERIC-PCR. 89 genotypes were determined. The Hunter Gaston Discriminatory Index (HGDI) attained 0.9995. Relationships analysis revealed that Group A B. cereus isolates tended to carry hblA, hblC, hblD, nheA, nheB, and show resistance to penicillin/trimethoprim/sulfamethoxazole. This study was useful for updating the knowledge of the contamination status of B. cereus in RTE rice products in China.